A Website Intervention to Increase Knowledge About Living Kidney Donation and Transplantation Among Hispanic/Latino Dialysis Patients. (March 2016) - Gordon, Elisa J.; Feinglass, Joe; Carney, Paula; Vera, Karina; Olivero, Maria; Black, Anne; O'Connor, Kate Grubbs; Baumgart, Jessica MacLean; Caicedo, Juan Carlos
Background: Hispanic dialysis patients often encounter barriers to learning about living kidney donation and transplantation. Effective culturally targeted interventions to increase knowledge are lacking. We developed a culturally targeted educational website to enhance informed treatment decision making for end-stage kidney disease. Methods: A pretest/posttest intervention study was conducted among adult Hispanic patients undergoing dialysis at 5 dialysis centers in Chicago, Illinois. Surveys included a 31-item, multiple-choice pretest/posttest of knowledge about kidney transplantation and living donation, attitudes about the website, Internet use, and demographics. The intervention entailed viewing 3 of 6 website sections for a total of 30 minutes. The pretest/posttest was administered immediately before and after the intervention. Participants completed a second posttest via telephone 3 weeks thereafter to assess knowledge retention, attitudes, and use of the website. Results: Sixty-three patients participated (96% participation rate). Website exposure was associated with a mean 17.1% same day knowledge score increase between pretest and posttest ( P < .001). At 3 weeks, participants' knowledge scores remained 11.7% above pretest ( P < .001). The greatest knowledge gain from pretest to 3-week follow-up occurred in the Treatment Options ( P < .0001) and Cultural Beliefs and Myths ( P < .0001) website sections. Most participants (95%) "agreed" or "strongly agreed" that they would recommend the website to other Hispanics. Conclusions: Web-based education for patients undergoing dialysis can effectively increase Hispanics' knowledge about transplantation and living kidney donation. Study limitations include small sample size and single geographic region study. Dialysis facilities could enable website access as a method of satisfying policy requirements to provide education about kidney transplantation.